PEMANFAATAN DAUN NANAS (ANANAS COMOSUS) SEBAGAI ADSORBEN LOGAM Ag DAN Cu PADA LIMBAH INDUSTRI PERAK DI KOTAGEDE YOGYAKARTA - Wardani, Ardi Yuli (Pelita - Jurnal Penelitian Mahasiswa UNY, 2015)
This research aims to determine the characteristics, the adsorption and the influence of the adsorbent from the leaves of pineapple (Ananas comosus) on the adsorption of metal Ag and Cu. The study is a basic experimental research. The subject the research is carbon from the pineapple leaves activated by the HCl 15% with a 24 hour immersion time. This research involved three steps. They are making carbon activated from pineapple leaves, characterizing the activated carbon and determine the adsorption towards Ag and Cu metal in the waste water of silver electroplating industry in Kotagede. The object of the research is the ability of the adsorbent from the pineapple (Ananas comosus) leaves for Cu and Ag adsorbs metals from the waste water of the silver industries in the town. The independent variable used is the amount of activated carbon, namely 0.5, 1.0, 1.5, 2.0 and 2.5 grams per 100 mL of liquid waste. Time and pH on the adsorption were carried out under optimum conditions, the contact time of 24 hours and at pH 2. The characterization of the activated carbon used the parameters of the water content, ash and absorption of I2. The adsorption was determined by comparing the concentrations of Cu and Ag before and after the adsorption . The research findings showed that the activated carbon from the pineapple (Ananas comosus) leaves consisted of 0.6% of moisture content, 3.2% of ash content and the absorption of I2 73.67%. For Cu the optimum adsorption was obtained in the adsorbent mass of 2 gram/100 mL with the adsorption power of 69.07% and for Ag the optimum adsorption was obtained in the adsorbent mass of 1.5/100 mL with the adsorption power of 74.56%. The increase in mass of adsorbent increased the adsorption power. Key words: adsorbents, pineapple leaf, liquid waste